A região Norte nos livros didáticos de geografia nos anos iniciais do Ensino Fundamental antes e após a implementação da Base Nacional Comum Curricular - Chignolli, Manoela (Universidade Federal de São Carlos, 2025)
The study analyzes how the Northern Region of Brazil is represented in Geography textbooks for the 3rd and 4th grades of Elementary School, comparing works from the periods of the National Curriculum Parameters and the Common National Curriculum Base. The research, of a qualitative and documentary nature, was based on the Pitanguá Mais collection (Moderna Publisher), approved by the National Textbook Program. The results show that, despite advances in thematic variety and content updating, descriptive and fragmented views of the Northern Region, focused on natural and cultural aspects, still predominate. It is concluded that the teacher's mediation is essential to broaden discussions and foster a critical and plural understanding of Brazilian sociocultural diversity.
The Northern region in geography textbooks for the early years of elementary education before and after the implementation of the national common core curriculum
Keywords: Livro-didático; Geografia; Região Norte; BNCC; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade